Evaluating Risk Factors for Clinical Failure Among Tigecycline-Treated Patients - Huang CF; Yang JL; Chuang YC; Sheng WH (Infection and Drug Resistance)
Chun-Fu Huang,1 Jia-Ling Yang,2 Yu-Chung Chuang,2,* Wang-Huei Sheng2,* 1Department of Internal Medicine, National Taiwan University Hospital Yun-Lin Branch, Yun-Lin, Taiwan; 2Department of Internal Medicine, National Taiwan University Hospital, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: Yu-Chung Chuang, Department of Internal Medicine, National Taiwan University Hospital, 7 Chung-Shan South Road, Taipei, 100, Taiwan, Tel +886-2-23123456 ext. 63015, Fax +886-2-23971412, Email weischuang@gmail.comPurpose: Clinical trials have documented that tigecycline has a higher mortality risk than other treatments; it continues to be widely used for various infections in real-world settings, where its associated risk factors for clinical failure are understudied.Patients and Methods: This retrospective analysis included a prospective 2019– 2021 cohort of tigecycline-treated patients, excluding those with multiple infection sites. We assessed the outcomes on day 28, with clinical failure defined by mortality, persistent initial infection symptoms, or the requirement for continued antimicrobial treatment. Multivariable logistic regression was used for the outcome analysis.Results: Of 253 patients included in the study, 94 experienced clinical failure. The infection foci included pneumonia (46.3%), bloodstream infection (BSI) (25.3%), and skin/soft tissue infections (10.3%). There were no significant differences in high-dose tigecycline administration or monotherapy rates between patients with favorable outcomes and those with clinical failure. A higher Charlson comorbidity index (adjusted odds ratio [aOR] = 1.20, P = 0.001), Pitt bacteremia score (aOR = 1.25, P = 0.007), and BSI (aOR = 3.94, P < 0.001) were significant predictors of clinical failure. Concomitant use of Pseudomonas aeruginosa-active fluoroquinolone (aOR = 1.97, P = 0.03) and carbapenem (aOR = 2.20, P = 0.01) was linked to increased clinical failure.Conclusion: Multiple comorbidities, BSI, and higher Pitt bacteremia scores are associated with increased risk of clinical failure in tigecycline-treated patients. These results suggest clinicians should consider alternatives to tigecycline for patients with these risk factors. When administering tigecycline, vigilant monitoring is indicated to manage potential clinical failures.Keywords: clinical response, predictors, tigecycline